Telemedicine for cardiovascular disease continuum: A position paper from the Italian Society of Cardiology Working Group on Telecardiology and Informatics. (1st April 2015) - Brunetti, Natale Daniele; Scalvini, Simonetta; Acquistapace, Flavio; Parati, Gianfranco; Volterrani, Maurizio; Fedele, Francesco; Molinari, Giuseppe
Abstract: Telemedicine is the provision of health care services, through the use of information and communication technology, in situations where the health care professional and the patient, or 2 health care professionals, are not in the same location. It involves the secure transmission of medical data and information, through text, sound, images, or other forms needed for the prevention, diagnosis, treatment, and follow-up of a patient. First data on implementation of telemedicine for the diagnosis and treatment of acute myocardial infarction date from more than 10 years ago. Telemedicine has a potential broad application to the cardiovascular disease continuum and in many branches of cardiology, at least including heart failure, ischemic heart disease and arrhythmias. Telemedicine might have an important role as part of a strategy for the delivery of effective health care for patients with cardiovascular disease. In this document the Working Group on Telecardiology and Informatics of the Italian Society of Cardiology intends to remark some key-points regarding potential benefit achievable with the implementation of telemedicine support in the continuum of cardiovascular disease. Highlights: Telemedicine could be useful for the management of cardiovascular disease in the entire cardiovascular continuum. Telemedicine pre-hospital electrocardiogram can shorten the delay to reperfusion and lower mortality of STEMI. Home monitoring of cardiac implantable electronic devices is associated with an early detection of adverse events.